2004
DOI: 10.1016/j.cardiores.2004.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric septal hypertrophy in heterozygous cMyBP-C null mice

Abstract: These data provide evidence that heterozygous cMyBP-C null mice represent the first model with a key feature of human FHC that is asymmetric septal hypertrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
152
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(180 citation statements)
references
References 36 publications
25
152
3
Order By: Relevance
“…Yet, we believe that prevention is the more realistic scenario in the patient group we would like to target with the gene therapy approach, namely infants with severe homozygous or compound heterozygous mutations who quickly develop a therapy-resistant form of systolic heart failure 14,[16][17][18][19][20] . Second, mouse models including our KI model clearly differ from human HCM in that they show a much milder phenotype, generally only at the homozygous state 8,40,41 . In fact, our KI mice, although likely the best murine HCM model available, have a normal life expectancy and, as shown also in this study, LVH and the decrease in LV contractile function remain stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, we believe that prevention is the more realistic scenario in the patient group we would like to target with the gene therapy approach, namely infants with severe homozygous or compound heterozygous mutations who quickly develop a therapy-resistant form of systolic heart failure 14,[16][17][18][19][20] . Second, mouse models including our KI model clearly differ from human HCM in that they show a much milder phenotype, generally only at the homozygous state 8,40,41 . In fact, our KI mice, although likely the best murine HCM model available, have a normal life expectancy and, as shown also in this study, LVH and the decrease in LV contractile function remain stable over time.…”
Section: Discussionmentioning
confidence: 99%
“…MyBP-C's role in cardiac function is still widely unknown but is suspected to contribute to ␤-adrenergic-mediated gains in function (105,357,771,772,839,840), myofilament Ca 2ϩ sensitivity (102,331,365,542), and length-dependent changes in myofilament Ca 2ϩ sensitivity (105,358). Additionally, MyBP-C must play a critical role in normal cardiac function as 20 -30% of inherited HCM cases are attributed to mutations in the gene that encodes for MyBP-C (226,638).…”
Section: Thick Filament Accessory Proteins: C-protein (Mybp-c)mentioning
confidence: 99%
“…For instance, a clinical study reported no detectable levels of MyBP-C in HCM patients with MyBP-C mutant alleles (760), suggesting that the mutated MyBP-C is unstable with a pathogenic mechanism leaning towards one of haploinsufficiency. A heterozygous MyBP-C null mouse model also lends some support to the mechanism of haploinsufficiency as a knockout of one MyBP-C allele resulted in a slight but significant decrease in total MyBP-C content (102). In contrast, the development of transgenic mouse models that have two-to eightfold overexpression of either wild-type MyBP-C or an HCM-linked truncated MyBP-C demonstrated that MyBP-C stoichiometry is conserved and that the truncated MyBP-C is indeed stable (990).…”
Section: Thick Filament Accessory Proteins: C-protein (Mybp-c)mentioning
confidence: 99%
See 1 more Smart Citation
“…One exception is a deletion of proximal myosin-binding protein-C sequences; heterozygous mutant mice exhibited normal heart structure while homozygous mutant mice developed hypertrophy (15). Remarkably, while most heterozygous mouse models with a mutation in myosin heavy chain, myosin-binding protein-C, or troponin T developed HCM (16)(17)(18), homozygous mutant mice (19,20) developed DCM with fulminant heart failure and, in some cases, premature death. These mouse studies might indicate that HCM, DCM, and heart failure reflect gradations of a single molecular pathway.…”
Section: Force Generation and Propagationmentioning
confidence: 99%